Modelling and Experimental Setup of a Cable Driven System - Eraz, Talha; Kiper, Gökhan; Eraz, Talha; Dede, Mehmet İsmet Can (Izmir Institute of Technology, 2016)
This study is about a single degree of freedom mechanism to be used for human arm rehabilitation purposes and actuated with cable-drive. The purpose of the design is to support rehabilitation motions with a single degree of freedom (dof) mechanism. Design criteria is set based on research and meetings with medical doctors. The desired design is an exoskeleton type system to support human arm on each moving part of it. The first designed four- bar mechanism had actuation problems. Torque requirement was unacceptably high near the singularity of the designed four-bar mechanism. This problem is later overcome by an extra dyad of two additional links. However, the extra dyad solution caused problems of back-drivability near the singularity of new dyad. In order to achieve a back-drivable four-bar mechanism that has a smooth actuation requirement through the motion, a novel cable actuation system is designed. Cable is attached to system on coupler link and the attachment point on the coupler is designed to achieve a straight path for the efficiency of the cable drive. However, a single straight line throughout the motion is not achievable. Therefore, path is divided into subsections of straight line paths. Intermediate pulleys are placed for cable to follow straight line sections. The cable is designed as closed loop. A prototype of the system is built and presented in last chapter.
Kablo Tahrikli Bir Sistemin Modellenmesi ve Deney Düzeneğinin Kurulması
Thesis (Master)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2016
Full text release delayed at author's request until 2018.08.15
Includes bibliographical references (leaves: 61-64)
Text in English; Abstract: Turkish and English
Keywords: Cable driven system; Medical doctors; Medical devices; Rehabilitation robotics